THE VARIATIONS IN BIOCHEMICAL PARAMETERS IN BLOOD AND MILK DUE TO MASTITIS INDICATION AND COWS PARITY (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
With the aim of determination of the variability of biochemical parameters in blood plasma and milk samples depending on mastitis incidence and parity, blood and milk samples were taken from 75 high-yielding Holstein cows. The mastitis incidence was defined accordingly to daily lactose content and daily somatic cell count (test-day records). The obtained results indicate that the differences between the analysed biochemical parameters in blood plasma, due to mastitis score classes (accordingly to daily somatic cell count, SCC) were present and statistically significant (P < 0.05) in some parameters (AST and GGT). Also, different patterns regarding mastitis scoring (DCL of SCC) were determined in some parameters. It was established that there was an increase in the levels of most of the analysed biochemical parameters in blood plasma and milk compared due to animal parity, except for TGC and Fe in blood plasma, and milk glucose where the concentrations were mostly lower in the following parity. Therefore, when using test-day records as an indicator for the mastitis risk and health status of an animal both scoring ways should be used, but in the case of mastitis risk or mastitis occurrence, other diagnostic methods (such as various mastitis tests) should be used for explicit detection.